Cytokine production in an ex vivo model of SARS-CoV-2 lung infection - Vorobyeva, Daria A.; Potashnikova, Daria M.; Maryukhnich, Elena V.; Rusakovich, George I.; Tvorogova, Anna V.; Kalinskaya, Anna I.; Pinegina, Natalia V.; Kovyrshina, Anna V.; Dolzhikova, Inna V.; Postnikov, Alexander B.; Rozov, Fedor N.; Sotnikova, Tatiana N.; et al. (Frontiers in Immunology, 2024)
Introduction The mechanisms of the SARS-CoV-2-triggered complex alterations in immune cell activation and production of cytokines in lung tissue remain poorly understood, in part because of the limited use of adequate tissue models that simulate the structure and cell composition of the lung in vivo. We developed a novel ex vivo model of SARS-CoV-2 infection of lung explants, that maintains the intact tissue composition and the viral load for up to 7–10 days. Using this model, we studied cytokine production during SARS-CoV-2 infection. Materials and methods Lung tissue was monitored for viability and cell composition using flow cytometry and histological analysis. SARS-CoV-2 infection was verified immunohistochemically, viral loads in tissue and culture medium were monitored by qPCR. A panel of 41 cytokines was measured in culture medium using xMAP technology. Results The explant lung tissue was viable and maintained viral infection that influenced the cytokine production. Elevated concentrations of G-CSF, GM-CSF, GRO-a, IFN-g, IL-6, IL-8, IP-10, MCP-3, MIP-1a, PDGF-AA, and VEGF, and decreased IL-1RA concentration were observed in infected tissue compared to non-infected tissue. Discussion Our results generally reflect the data obtained in COVID-19 patients. GRO-a, IFN-g, IL-6, IL-8, MCP-1, MCP-3, and RANTES correlated with the viral load, forming a distinct pro-inflammatory cluster. Thus, our lung ex vivo model faithfully reproduces some aspects of cytokine alterations in COVID-19 patients at an early disease stage, making the investigation of SARS-CoV-2 infection mechanisms more accessible and providing a potential platform for antiviral drug testing.